Lack of anti-paternal cytotoxic antibody production in the presence of spermatozoa in recurrent spontaneous abortion couples in contrast to fertile couples: a pilot study - Mitra Rafiee; Nasrin Sereshki; Razieh Alipour; Vahid Ahmadi Panah; David Wilkinson (IMR Press, 2021)
Background: Anti-paternal cytotoxic antibody (APCA) is a pregnancy alloantibody and is directed to paternal HLA molecules. A recent study showed that this antibody is produced in the presence of the husband's spermatozoa. Several studies have shown the absence or reduction of this antibody in the serum of recurrent spontaneous abortion (RSA) women. Note that the production of APCA has not been determined in the presence of spermatozoa in RSA women. A reason for the reduction or absence of APCA in the serum of RSA women may be the inability of the husband's spermatozoa to induce APCA production by lymphocytes. Therefore, this study aims to investigate APCA production by the wife's peripheral blood mononuclear cells (PBMCs) in the presence of the husband's spermatozoa in RSA couples. Methods: Ten RSA couples and ten fertile couples were included in this study. The wife's PBMCs (peripheral blood mononuclear cells) were cocultured with her husband's spermatozoa and the supernatant assessed for the presence of IgG by the ELISA method and APCA by complement-dependent cytotoxicity (CDC) assay. Results: Results showed that the production of IgG (median = 740 ng/mL in the fertile and 64 ng/mL in the RSA group) and APCA (median = 78% in the fertile and 48.5% in the RSA group) was significantly lower in the RSA group as compared to the fertile group. Conclusions: We concluded that a possible cause for APCA reduction in RSA women may be the inability of the husband's spermatozoa in induction of antibody production by the wife's PBMC. Nevertheless, large studies are needed to confirm the results of the present study.